Viral determinants of enterovirus 71 neuroinvasive potential - Rachel (2018)
Enterovirus 71 (EV71) is a virus that commonly results in Hand, Foot and Mouth disease (HFMD) and often affects young children. Over the years, it has been observed that affected individuals not only manifest the viral infection as HFMD but neurological complications are often associated with them. However, our understanding of the mechanisms of EV71 infection is still limited. To assess the functional significance of mutations identified in the 5’UTR from a previous experiment in a mouse-model of infection, we generated 10 infectious clones with point mutations in an otherwise homogenous genetic background. A clinical isolate of EV71 strain 41 wild type (WT) together with the infectious clones were used to determine the relative expression of EV71 in human rhabdomyosarcoma (RD) cells. Quantitative Reverse Transcription Polymerase Chain Reaction (RT-qPCR) was employed for quantification of EV71. The results obtained using unpaired t-test indicate that growth kinetics of the infectious clones did not differ significantly (p>0.05) compared to WT. A Plaque Assay was done on selected infectious clones, including the WT and the results show an absence of infectious particles, which was an unexpected result and indicative of a flaw in our initial experimental design. Subsequent experiments were performed to explain the phenomenon.